Answer:
The value for the expression [tex](A+B)^{2}[/tex] is the largest
Step-by-step explanation:
Since both A and B must be greater than 0 and A>B then we can assume the least possible values for B=1 and A=2.
So,
i) 2(A+B) = 2(2+1) = 2*3 = 6
ii) [tex](A+B)^{2}[/tex] = (A+B)*(A+B) = (2+1)*(2+1) = 3*3 = 9
iii) [tex]A^{2} + B^{2}[/tex] = [tex]2^{2} +1^{2}[/tex] = 4+1 = 5
iv) [tex]A^{2} - B^{2} = 2^{2} - 1^{2}[/tex] = 4-1 =3
Inspecting the answers of the above four expressions, we see that the value for the expression [tex](A+B)^{2}[/tex] is the largest.